The Students’ Reading Comprehension At SMP Negeri 5 Pematangsiantar - Marhaeni Kartika Dewi Matondang; Tiodora Fermisaka Silalahi; Kesia Silaban (Program Studi Pendidikan Bahasa Inggris FKIP, 2024)
The aim of this research was to find out the use of comic strip for improving the students’ reading comprehension of seventh grade students at SMP NEGERI 5 PEMATANGSIANTAR. This research was classified as a true-experimental study. It involved 30 students from two groups, Class VII7 (15 students) as control group and Class VII8 (15 students) as the experimental group. The control group was students taught using conventional technique whereas the experimental group was students taught using of comic strip. The data were obtained by using pre-test and post-test. The data of the pre-test and post-test of both groups were analyzed by using inferential statistics (SPSS 24). The result of the research shows that the testing hypothesis of post-test score, it is found that that tcount (.491) >ttable (2.172) at the significance level α =0.05 with the degrees of freedom (df) = 14, Ho is rejected and Ha is accepted. It means that there are the improving in students learning by using Comic Strip For Improving The Students’ Reading Comprehension At SMP Negeri 5 Pematangsiantar